Discrepancy between VIA Screening and HPV DNA Status: A Real-World Evidence from a Large-Scale Program - Rohmawati, Indah; Setiawan, Aris; Krisdyana, Bekti; Ningtiyasari, Nunik (Journal of Health Sciences and Epidemiology, 2026)
Cervical cancer is a significant health issue in low- and middle-income countries (LMICs). Visual Inspection with Acetic Acid (VIA) is commonly used for screening because of its affordability. This study analyzed the association between reproductive factors, Human Papillomavirus (HPV) DNA status, and VIA results among 860 women in Tulungagung, Indonesia. The participants had a mean age of 41 years, and 48% used hormonal contraceptives. Most respondents had negative VIA results (94.1%) and negative HPV DNA status (90.7%). Bivariate and multivariate analyses showed no significant associations between VIA results and HPV DNA (p=0.262), age (OR=0.747, p>0.05), or contraceptive use. Diagnostic analysis revealed that VIA had a high specificity (94.4%) but very low sensitivity (8.8%) when compared to HPV DNA status. The high false-positive rate (86.3% of VIA-positive cases were HPV-negative) highlights VIA's limitations of VIA in terms of objectivity. In conclusion, reproductive factors and HPV DNA were not significant predictors of VIA outcomes. Transitioning toward HPV DNA testing as a primary screening tool is recommended to improve program accuracy.